Ultrasonic Characterization of Ferrous Ammonium Sulphate in Aqueous Galactose Solutions - WADHWANI, VARSHA; DHARI, VISHNU (Asian Journal of Chemistry, 2010)
Ultrasonic velocities and densities of aqueous ternary solutions containing ferrous ammonium sulphate (0.0 to 1.0 M) and aqueous galactose (0.0, 0.5 and 1.0 M) at 308 K have been measured using ultrasonic interferometric and pyknometric techniques. The experimental data have been used to calculate several ultrasonic parameters viz., adiabatic compressibility (βs), inter molecular free length (Lf), molar sound velocity (R), specific acoustic impedance (Z) and hydration number (Hn). The results have been interpreted in terms of structure making (SM) and structure breaking (SB) properties of ferrous ammonium sulphate in aqueous galactose solutions